Ujarzmić kulturę: literaturoznawczy darwiniści i biologiczne podstawy humanistyki - Stopel, Bartosz (Er(r)go. Teoria - Literatura - Kultura, 2014)
Bartosz Stopel Subjugating Culture: Literary Darwinists and the Biological Roots of Humanities The article analyzes the relation between nature and culture in the light of Darwinian literary studies. According to the Darwinists, literary theory has greatly suffered from claiming that culture (in the sense of the whole of human creation) is autonomous in relation to nature. If, as they claim, the human psyche is not independent from the biologically understood body, and if the theory which best explains the functioning of the human mind is evolutionary psychology, then all its creations (including literature and other arts) can be fully understood only within Darwinian framework. As the Darwinists claim, understanding the mechanisms governing art, along with its function in human life requires subordinating humanities to biology and a further reduction of all research areas to simpler, empirical claims, so that the unity of science can be maintained. However, a closer analysis of both the Darwinists’ claims and of some examples of the Darwinian studies indicates numerous problems with the postulated research programme, raising doubts about the possibility of a fully reductionists stance on culture.